Macro‐encapsulation of mesenchymal stem cells in acute and chronic liver injury animal models. Issue 7 (18th February 2021) - Kang, Hyeon Tae; Jang, Kiseok; Jun, Dae Won; Yoon, Eileen L; Lee, Seung Min; Saeed, Waqar Khalid; Lee, Jin Ho
Abstract: Background and Aim: Stem cell treatments using scaffolds for liver disease have been well studied. However, macro‐encapsulation of mesenchymal stem cells (MSCs) to minimize or inhibit stem cell homing has not been evaluated. Here, we conducted a proof‐of‐concept study using MSCs macro‐encapsulated in poly lactic‐co‐glycolic acid in liver disease models. Methods: Poly lactic‐co‐glycolic acid semipermeable membranes (surface pore size up to 40 μm) were used as the macro‐encapsulation system. Macro‐encapsulated pouches were loaded with MSCs and sealed. Each pouch was implanted in the subcutaneous region of the dorsum or interlobular space of the liver. Acute liver injury was induced using thioacetamide intraperitoneal injection thrice a week. For the chronic liver fibrosis model, thioacetamide dose was gradually increased, starting from 100 to 400 mg/kg over 16 weeks (thrice a week). Results: In the acute liver injury model, the treated groups showed decreased liver inflammation and necrosis compared with the control. Hepatic fibrosis decreased in the treated group in the chronic liver fibrosis model compared with that in the control group. Encapsulated MSCs exhibited changed cell morphology and characteristics after implantation, showing increased periodic acid–Schiff staining and CYP2E1 expression. Migration and homing of MSCs into the liver was not observed. Under hypoxic conditions, macro‐encapsulated MSCs secreted more growth hormones, including vascular endothelial growth factor, platelet‐derived growth factor, angiopoietin‐2, and placental growth factor, than monolayered MSCs in vitro . Conclusions: Macro‐encapsulated MSCs attenuate hepatic inflammation and fibrosis by upregulating hypoxia‐induced growth hormone secretion in liver disease models.